The influence of paper surface sizing on inkjet pigment penetration - Costa, Tiago G. (2010)
The effect of paper surface sizing on inkjet pigment penetration was evaluated by studying four different paper samples: one taken as reference, without surface sizing (paper RP), one surface sized with cationic starch (RPS1), one with a mixture of cationic starch and poly(styrene-co-maleic anhydride) (RPS2), and one with a mixture of cationic starch and poly(styreneco- acrylate) (RPS3). Assessment was based on the grey level analysis of a black printed area on the top surface of the paper samples and on internal layers below that printed area (obtained by delamination of the paper sheets). From the grey level distribution curves it was possible to confirm that the majority of the ink was retained at the top surface, as expected. The penetration degree of the ink pigment was RPS1 < RPS3 << RPS2 << RP and the results were found to be related to the polar component of the surface energy. The ink penetration into the paper sheets was less pronounced for the papers with a higher surface polar character due to the stronger interactions between the water based ink and the surface sizing agents. The highest ink penetration was observed for sample RP due to the very low polarity (and lower topographical uniformity) of its surface.